2011
DOI: 10.1007/s10228-011-0208-4
|View full text |Cite
|
Sign up to set email alerts
|

Habitat factors affecting the distribution and abundance of the spinous loach Cobitis shikokuensis in southwestern Japan

Abstract: We examined habitat factors related to the distribution and abundance of the spinous loach Cobitis shikokuensis, an endangered benthic fish, in the Shigenobu River system, southwestern Japan. In the study river, the spinous loach was distributed widely along the main stem, from headwater to near the mouth, whereas it was rarely found in tributary streams. Classification tree analysis showed that the presence/absence of spinous loach was explained by a combination of percent pebble and length of river fragment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…From the mid-to lower reaches of the river, the channel is braided (bankfull width approximately 300 m maximum), and the flow tends to be intermittent owing to a thick channel layer of alluvial deposits. At present, there are three intermittent reaches in the river (upper: 18–22 km from the mouth; middle: 10–16 km; and lower: 4.9–7.4 km) (Kawanishi et al, 2011). Macroinvertebrate samples were collected from 10 sites longitudinally located from the headwater to the lower reaches of the Shigenobu River (elevation range: 4–405 m; Table 1, and Fig.…”
Section: Methodsmentioning
confidence: 99%
“…From the mid-to lower reaches of the river, the channel is braided (bankfull width approximately 300 m maximum), and the flow tends to be intermittent owing to a thick channel layer of alluvial deposits. At present, there are three intermittent reaches in the river (upper: 18–22 km from the mouth; middle: 10–16 km; and lower: 4.9–7.4 km) (Kawanishi et al, 2011). Macroinvertebrate samples were collected from 10 sites longitudinally located from the headwater to the lower reaches of the Shigenobu River (elevation range: 4–405 m; Table 1, and Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, during the field investigation for our previous study (Kawanishi et al. ), we found no C . shikokuensis individuals in tributaries where the catchment had been largely converted to agricultural lands (R. Kawanishi, unpublished data).…”
Section: Discussionmentioning
confidence: 52%
“…This loach is thought to be affected by habitat degradation caused by human activities and has been designated as endangered by the Ministry of the Environment. Our previous study revealed that among-reach variations in the abundance of C. shikokuensis within a river system were primarily related to substrate conditions (Kawanishi et al 2011). We also reported selective use of sediment-free substrate by this species (Kawanishi et al 2010).…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations